Competition and antibiotics prescription - Sara Fogelberg; Jonas Karlsson (Research Institute of Industrial Economics (IFN), 2012)
The introduction of antibiotics as a medical treatment after World War II helped to dramatically increase life expectancy in the industrialized world. As a consequence of over-prescription the last decades ave however seen a sharp increase in prevalence of multi-resistant bacteria, disarming once powerful anti-pathogens. This paper investigates the effect of increased competition between healthcare providers on prescription of antibiotics. We make use of a competition- inducing reform implemented in different counties in Sweden at different points in time during 2007 to 2010. Our dataset contains monthly data on all prescribed antibiotics in Sweden which makes us able to estimate the effects on all antibiotics prescribed, as well as different subcategories of antibiotics. The results indicate that increased competition had a positive and significant effect on antibiotics prescription.
Keywords: C23; H30; I11; I18; 330; Healthcare; competition; competition reform; antibiotics